The Protective Effects of Borax on Doxorubicin Induced Cardiotoxicity in Rats - Çelikezen, Burçin; Tanyıldızı, Sadettın; Oto, Gokhan (My University, 2021)
Boron and boron compounds have benefical effects on health of human and animals.This study was designed to determine the protective effect of borax (BX) in doxorubicin (DXR) induced cardiotoxicity in rats. In this study, 20 Wistar-Albino male rats* were used. The rats were divided into four groups including 5 rats in each one; control group (standard pellet food + water + normal saline), doxorubicin (3.75 mg/kg/ip, single dose in a week), doxorubicin + borax (3,75 mg/kg/ip + 25 mg/kg/oral/ respectively), and borax (25 mg/kg/oral, single dose in a week). At the end of the experiment, to evaluate antioxidant activity MDA, GSH, CAT, SOD levels determined in blood samples of rats. Besides, CK levels were investigated to determine the effect of doxorubucine on heart tissue. According to the results, MDA levels increased significantly in doxorubucin induced group (p<0.05). After borax treatment MDA status decreased under the control values (p<0.05). GSH status decreased in all groups. While CAT level decreased in DXR induced group in a statistically important rate (p<0.05), it was observed near control values in BX and BX+DXR induced groups. SOD status indicated increase in BX and DXR groups. In addition, CK levels increased in all groups compared to the control. In the increases only in DXR induced group, significance was determined as p<0.05. As a result, these data indicated that borax may use to prevent cardiotoxic effect of doxorubicin.
Keywords: Rat; Borax; Doxorubicin; Boron Compounds; Cardiotoxicity